Volbots: Volvox Microalgae‐Based Robots for Multimode Precision Imaging and Therapy. (19th June 2022) - Wang, Jie; Soto, Fernando; Liu, Shiqin; Yin, Qingqing; Purcell, Emma; Zeng, Yitian; Hsu, En‐Chi; Akin, Demir; Sinclair, Bob; Stoyanova, Tanya; Demirci, Utkan
Abstract: Biohybrid microrobotics are exploited as a delivery approach to actively transport therapeutic payload to tumors. However, the therapeutic utility of this approach can be diminished by tumor hypoxia. Moreover, current biohybrid microrobotics design is mainly focused on the living organisms' motility and biocompatibility, yet the unique biological function of the natural organism is often overlooked. Here, an all‐in‐one self‐propelled volvox‐based multifunctional robot, that is, Volbot, with built‐in capabilities of fluid mixing, multimode imaging, and photosynthesis‐mediated in situ oxygen generation that can potentially relieve hypoxia is developed. Volbots can follow a pre‐specified route and directionality under the control of a magnetic field. Red‐light irradiation (λ = 650 nm) can enhance the Volbot's locomotive behavior, enhance the mixing of biofluids, and modulate the oxygen production to improve the efficacy of photodynamic therapy. Moreover, Volbots can absorb near‐infrared irradiation and produce localized hyperthermia to treat tumors. Subcutaneous tumor suppression can be achieved by this high‐yield oxygen‐producing biohybrid "microfactory" in a photodynamic/photothermal‐synergistic therapy strategy. Furthermore, Volbots also offer imaging capabilities and exhibit considerable promise as a multifunctional microrobotics‐based theranostic approach for a precision tumor therapy strategy. Abstract : An all‐in‐one self‐propelled volvox‐based multifunctional robot, with built‐in capabilities of fluid mixing, multimode imaging, and photosynthesis‐mediated in situ oxygen generation that can potentially relieve hypoxia is developed.